Analysis of Early Detection of Growth and Development in Toddlers at Simpang Gambir Health Center, Mandailing District - Dewi Mega Br. Simbolon; Paninsari, Debora; Sucitrawaty, Qisthi Aulia; Rangkuti, Suciana; Br. Sitepu, Sari Dayang (INDOGENIUS, 2026)
Background & Objective: Toddlerhood is a golden period that significantly influences a child’s future growth and development. One key effort to detect developmental delays is through the Early Detection and Intervention for Growth and Development (SDIDTK) program. Low program coverage in certain areas, including the Simpang Gambir Community Health Center, calls for an evaluation of its implementation. Method: This study used a quantitative approach with a descriptive-analytic design. A total of 30 toddlers registered at the Simpang Gambir Health Center were selected as samples. Data were analyzed using univariate and bivariate methods with the chi-square test to assess the relationship between birth weight, nutritional status, family income, and parental education with developmental status. Result: Most toddlers (24 out of 30, or 80%) demonstrated development appropriate to their age. Bivariate analysis revealed no significant relationship between birth weight (p = 0.169), nutritional status (p = 0.169), or family income (p = 0.531) and developmental status. However, parental education showed a near-significant association (p = 0.059), indicating its likely impact on toddler development. Conclusion: Most toddlers showed appropriate development. Although birth weight, nutrition, and income were not significantly related, parental education likely influences developmental outcomes and should be a focus of future interventions.